A curious property of series involving terms of generalized sequences - Odoardo Brugia; Piero Filipponi (International Journal of Mathematics and Mathematical Sciences)
Here we are concerned with series involving generalized Fibonacci numbers Un  (p,q) and generalized Lucas numbers Vn  (p,q). The aim of this paper is to find triples (p,q,r) for which the series Un  (p,q)/rn and Vn  (p,q)/rn (for r running from 0 to infinity) are unconcerned at the introduction of the factor n. The results established in this paper generalize the known fact that the series Fn/2n (Fn the nth Fibonacci number) and the series nFn/2n give the same result, namely −2/5.